Implementation of the Evaluation of the Free Nutritious Meal Program (MBG) at SMP X Blambangan Umpu - Elpin Nurul Rahmayani; Salsabila Salsabila; Dimas Yulian; Undang Rosidin; Handoko Handoko (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The Free Nutritious Meal Program (MBG) is a national policy aimed at improving students’ nutritional status and supporting their readiness to learn at school. This study aims to evaluate the implementation of the MBG Program at SMP X Blambangan Umpu using the CIPP evaluation model (Context, Input, Process, Product). This research employed a descriptive qualitative approach, with research subjects consisting of teachers, students, parents/guardians, and MBG program managemant staff. Data were collected through observation and in-depth interviews to obtain a comprehensive picture of program implementation. Data validity was ensured using the interactive model of Miles, Huberman, and Saldana, wich includes data reduction, data display, and conclusion drawing. The results show that in the context component, the MBG Program is relevant to stundents’ nutritional needs and aligned with government policies, although menu variety still needs to be improved. In the input component, the readiness of humen resources, the involvement of nutritionists, and the availability of facilities and infrastructure were considered adequate however, students’ acceptance of the menu varied. In the process component, program implementation was fairly well organized, with effective mechanisms for quality control and food safety supervision. In the product component, the MBG Program had a positive impact on students’ eating patterns, stamina, and learning readiness, although improvements in nutritional status occurred gradually. Overall, the MBG Program contributes to supporting students’ health and the learning process therefore, continuous evaluation is needed to enhance the effectiveness of the program.